Evaluation of Interleukin-31 Serum Levels in Patients with Chronic Kidney Disease on Hemodialysis with and without Uremic Pruritus - Abdulqahar, Mustafa Sh.; A. Kasem, Ali (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Interleukin-31 has been linked with developing and maintaining pruritus in various dermatological and non-dermatological diseases. Objectives: To evaluate interleukin-31 serum levels in hemodialysis patients with and without uremic pruritus as a potential contributor. Methods: This cross-sectional study involved ninety adult chronic kidney disease patients on hemodialysis. All of the enrolled patients were on a three-times/week hemodialysis regimen. Patients were divided into two groups of 45 patients each. Group 1 involved those with pruritus and Group 2 involved those free of pruritus; based on the itching severity scale (ISS). Serum levels of interleukin-31, intact parathormone, urea, creatinine, and calcium were assessed before the hemodialysis session. Serum interleukin-31 levels were also assessed after the hemodialysis session. The statistical analysis was performed using the Statistical Package for Social Science (SPSS). The median and interquartile range (IQR) were used to present data on the continuous variables. Mann-Whitney test was used to compare the differences between medians of the two groups, and Wilikson test was used to compare the differences between medians of IL-31 before and after hemodialysis. Spearman’s correlation was employed to assess the correlation among the studied variables. A P-value less than 0.05 was considered significant. Results: In the pre-dialysis samples, serum levels of interleukin-31 in patients with uremic pruritus were not significantly different from those in patients without uremic pruritus [1361.55 (741.96) pg/mL and 1395.75(624.75) pg/mL, respectively; P=0.36]. However, patients with uremic pruritus had higher serum creatinine levels than patients without uremic pruritus [9.8(5.5) mg/dL and 8.15(3.18) mg/dL, respectively; P=0.02]. The two groups had no significant differences in intact parathormone, calcium, or urea serum levels. In both of the study groups, serum interleukin-31 levels in patients with and without uremic pruritus were significantly reduced by hemodialysis. In the post-dialysis samples, serum interleukin-31 levels in patients with uremic pruritus were not statistically different from those in patients without uremic pruritus [864 (164.58) pg/mL and 879.7(84.19) pg/mL, respectively; P=0.83]. Conclusions: The association of serum interleukin-31 levels with uremic pruritus in chronic kidney disease CKD patients on hemodialysis need further verification.